To the question of then cylindrical shells calculation with reinforcements and variable thickness - Brynza, A. A. (Science and Transport Progress, 2009)
In the article the calculations of cylindrical shells with reinforcements and variable thickness are considered. The use of method of solving the differential equations with variable factors offered by V. A. Lazaryan and S. I. Konashenko allows to shorten greatly the computing procedure but in a number of cases, having the big practical importance, to find the analytical decision.